Assessment of seed quality and sex determination in hop seedlings using molecular markers - Machado, Marília Pereira; Belniaki, Andreza Cerioni; Bernert, André Felipe; Gomes, Erik Nunes; Filho, João Carlos Bespalhok; Panobianco, Maristela; Deschamps, Cícero (Ciência e Natura, 2022)
Brazil is the world's third largest beer consumer and currently imports all of its hops for the brewing industry. Such a fact justifies the selection of hop genotypes adapted for cultivation locally, which requires high quality seeds and efficient sex determination of the seedlings. The objectives of this study were to develop a methodology to assess hop seed quality and to efficiently determine hop seedling sex through the use of male-specific molecular markers. Freshly harvested hop seeds were germinated with and without pre-chilling (3-5 ° C) for 3, 6 and 12 weeks and then germinated at 20 or 25 ° C in the presence or absence of light, evaluating germination percentage and germination speed index. F1 progenies were obtained from after seed germination in a greenhouse and seedlings sex was determined using male-specific molecular markers. The best conditions for physiological quality assessment of hop seeds used in the present study were pre-chilling for 12 weeks, followed by germination at 25 ° C, and normal seedling counts at 7 and 15 days. The progeny submitted to molecular marker sexing was composed of 61.3% female plants. The established methodologies presented here can be considered efficient and may contribute to expedite hops breeding programs.